2021
DOI: 10.3748/wjg.v27.i14.1507
|View full text |Cite
|
Sign up to set email alerts
|

T-tubevsno T-tube for biliary tract reconstruction in adult orthotopic liver transplantation: An updated systematic review and meta-analysis

Abstract: BACKGROUND Whether to use a T-tube for biliary anastomosis during orthotopic liver transplantation (OLT) remains a debatable question. Some surgeons chose to use a T-tube because they believed that it reduces the incidence of biliary strictures. Advances in surgical techniques during the last decades have significantly decreased the overall incidence of postoperative biliary complications. Whether using a T-tube during OLT is still associated with the reduced incidence of biliary strictures needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…In order to overcome the technical difficulty, using ductoplasty techniques or T-tube insertion was at the discretion of the surgeon. As previously shown, none of these technical refinements were associated with a reduced ABS rate ( 32 34 ).…”
Section: Discussionmentioning
confidence: 65%
“…In order to overcome the technical difficulty, using ductoplasty techniques or T-tube insertion was at the discretion of the surgeon. As previously shown, none of these technical refinements were associated with a reduced ABS rate ( 32 34 ).…”
Section: Discussionmentioning
confidence: 65%
“…A recent nationwide Italian survey [ 19 ] has reported that 25% of Italian LT Centers use it systematically, while 55% use it selectively; another international survey [ 20 ] has reported a 33.3% prevalence of T-tube use among LT Centers within the Eurotransplant, Swisstransplant, Scandiatransplant, and British Transplant Society networks. Several systematic review and meta-analysis [ 16 18 , 21 , 22 ] have shown that the overall use of T-tube does not significantly modify the risk of developing either biliary leak or stricture after DDLT. Even in the present study, the prevalence of biliary complications was decreased in the T-tube group, but not at a statistically significant level.…”
Section: Discussionmentioning
confidence: 99%
“…36 A recent meta-analysis by Zhao et al concluded that there was not enough evidence to support routine T-tube placement during LT in adults for the prevention of biliary strictures. 37…”
Section: Management Preventionmentioning
confidence: 99%
“…Zhao et al demonstrated that the use of a T-tube did not reduce the incidence of AS yet appeared to increase the development of overall biliary complications, including cholangitis. 37 Because AS are unifocal, short-segment, and located within the extrahepatic bile duct, they are easily amenable to endoscopic therapy. Both endoscopic therapy and PTBD have similar initial success rates, but long-term recurrence rates may be higher with PTBD.…”
Section: Anastomotic Stricturesmentioning
confidence: 99%